Risk levels of microplastic pollution in surface water and sediments at Ba Be Lake - Duong, Tuan Manh; Thai, Thi Linh; Nguyen, Ha Giang; Nguyen, Thi Khanh Linh; Vu, Hai Huong; Le, Xuan Thanh Thao; Duong, Thi Thuy; Do, Van Manh (Hue University Journal of Science: Natural Science, 2025)
Microplastics, plastic particles smaller than 5 mm, have become a serious issue in lake water environments, negatively affecting ecosystems and water quality. This study on microplastic pollution levels in the surface water and sediments of Ba Be Lake provides essential insights into the pollution status in this area. The results reveal that microplastic concentrations in surface water range from 2.1 ± 0.4 to 14.2 ± 8.9 particles/m³, and sediment contains from 29.5 ± 25.1 to 552.1 ± 760.6 particles/kg of dry weight. This indicates that microplastics tend to accumulate in sediment rather than remain suspended in the water column, resulting in a markedly higher abundance in benthic environments. Fibre-shaped microplastics dominate, and smaller particles account for the majority, indicating a diverse origin and easy dispersion in the environment. Fourier-transform infrared microscopy analysis helped to identify common types of microplastics in surface water and sediments, including urea-formaldehyde condensate, cellophane, polypropylene, and polyacrylamide. High-density microplastics tend to settle more into sediments, which may affect their transport and accumulation in the environment. The risk index of the detected polymers shows that the polymer hazard index scores for surface water and sediment in Ba Be Lake are 1024.2 and 1814.6, respectively, both classified under pollution level V (extremely hazardous). This indicates a significant threat to human health and ecosystems. These findings enhance the understanding of microplastic pollution in Ba Be Lake and support environmental managers in developing practical solutions to control and mitigate pollution in the area.